Photoprotective Effects of Epigallocatechin Gallate on Ultraviolet-Induced Zebrafish and Human Skin Fibroblasts Cells - Jie Zhang; Yahui Xu; Xiyu Ruan; Ting Zhang; Minghui Zi; Qiao Zhang (Hindawi Limited, 2024)
Background. The long-term exposure to ultraviolet radiation (UVR) raises oxidative stress and chronic inflammation levels, which in turn has a series of deleterious effects on skin health, such as sunburn, photoaging, and skin cancer. Hence, our study was determined to investigate the effects and mechanisms of epigallocatechin gallate (EGCG) in zebrafish and human skin fibroblasts (HSF) cells to alleviate ultraviolet-induced photoaging. Methods. The 4 days postfertilization (dpf) zebrafish larvae and HSF cells were treated with 10 J/cm2 UVA + 30 mJ/cm2 UVB, or 25, or 50 μM EGCG for 72 hr. The indicators involving in oxidative stress, inflammatory, and photoaging were measured by the kits, ELISA Kits and western blot methods. Results. EGCGs protect against UVR-induced skin damage in zebrafish and HSF cells. EGCG markedly decreased the reactive oxygen species (ROS), malondialdehyde, 8-OHdG levels, increased superoxide dismutase (SOD) activity, and significantly inhibited inflammatory factors levels including tumor necrosis factor-α (TNF-α), interleukin-1α (IL-1α), interleukin-6 (IL-6) in zebrafish, and HSF cells irradiated with UVR. We found that EGCG could reduce UVR-induced p38 mitogen-activated protein kinase (p38 MAPK) phosphorylation and effectively inhibited the activity of the transcriptional factor nuclear factor-κB (NF-κB), thereby reducing the protein-1 (AP-1), TNF-α, IL-1α, IL-6, and matrix metalloproteinase-1 (MMP-1) expressions, which are critical mediators of skin aging cascade causing the photoaging. Conclusion. These results validate that EGCG for protection of photoaging in zebrafish and HSF cells induced by UVR, which is closely related to the regulation of p38 MAPK/NF-κB, AP-1 signaling pathway which relieve oxidative stress, inflammation, and collagen degradation.